E-Commerce as Indonesia's Economic Development Effort - Cici Widya Prasetyandari (Indonesian Journal of Economics and Management, 2022)
Businesses need a technology for communication, recording company finances, monitoring employee performance, marketing the business, selling merchandise and others. The technology used in a business adapts to the needs of the company. Indonesia is one of the countries that use technology in various activities. This country is also one of the countries with the largest internet users in the world. The number of internet users is used by business people to market their products through e-commerce. This study aims to determine the role of e-commerce in helping the Indonesian economy. The method used is a literature review. The result is that e-commerce has a positive role for the Indonesian economy. The existence of e-commerce is able to increase income for entrepreneurs so that it can help the economy of the Indonesian people. In addition, e-commerce is also beneficial for consumers who want to shop without having to leave the house.